Malaysian graduates: what and why - Darmi, Ramiza; Albion, Peter (2013)
Malaysians are bilingual, many are trilingual while a few are multilingual; language is essential for communication and to make connection. What do the local graduates need to equip themselves upon graduation? Communication skills as one of the soft skills, in particular the English language are important which is introduced and incorporated into the curriculum of English language courses in public universities in Malaysia. Why is the number of unemployed Malaysian graduates on the rise? The local graduates have done well academically but language proficiency and communication skills seem to be the competitive factors to secure jobs. This article discusses the needs for Malaysian graduates to be competent users of English language. It also draws some of the challenges in teaching English language to Malaysian learners.